2017
DOI: 10.1515/rebs-2017-0050
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Exchange Market Efficiency In Botswana

Abstract: Wickremasinghe (2008) and Çiçek (2014) in which weak form was found to exist whilst the semi-strong form was found not to exist. This paper has filled an important gap as it is the first study to investigate the efficiency of the foreign exchange market in Botswana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Matebejana, Motlaleng, and Juana (2017) tested EMH for Botswana using a bilateral monthly exchange rate of Botswana's currency pula against South African rand, U.S. Dollar, British Pound, and Yen between 2000 and 2015. Using unit root tests, they verified weak‐form EMH in all series except for the British Pound.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Matebejana, Motlaleng, and Juana (2017) tested EMH for Botswana using a bilateral monthly exchange rate of Botswana's currency pula against South African rand, U.S. Dollar, British Pound, and Yen between 2000 and 2015. Using unit root tests, they verified weak‐form EMH in all series except for the British Pound.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author found that the market was consistent with the W-form of EMH but not with the SS-form of EMH and the investors in this market could earn a supernormal profit in short-run as well as in long-run. Matebejana et al (2017) first time investigated the efficiency of FEM in Botswana taking monthly exchange rate data of the South African rand, the American dollar, British pound and the Japanese yen against Botswana's currency pula covering the period 2000:01 to 2015:12. By using unit root tests (ADF, PP, KPSS) they have instituted that the FEM of Botswana was showed the evidence of the EMH in W-form except for the British pound, and by using Johansen cointegration test, they had not concluded about the existence of the SS-form of the EMH in the FEM of Botswana.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most relevant contribution is related to the study of the reversal of the average in the international exchange markets, aiming to understand the different predictability between them, in the context of the global pandemic . As far as we know the authors Ning, Wang, and Su (2017), Matebejana, Motlaleng, and Juana (2017), Njindan Iyke (2019), Chaudhry, Hanif, Hassan, and Chani (2019), analyzed the reversal to the average in the foreign exchange markets, testing the random walk and, efficient market hypotheses, in its weak form, but the research questions, the markets analyzed, the sampling period, and the estimation models were different from the following in this trial.…”
Section: Introductionmentioning
confidence: 99%